Late Pleistocene and Holocene groundwater flow history in the Baltic Artesian Basin: a synthesis of numerical models and hydrogeochemical data - Vaikmäe, Rein; Parn, Joonas; Raidla, Valle; Ivask, Juri; Kaup, Enn; Aeschbach, Werner; Gerber, Christoph; Lemieux, Jean-Michel; Purtschert, Roland; Sterckx, Arnaud; Martma, Tonu; Vallner, Leo (Estonian journal of earth sciences, 2021)
We review our current understanding of groundwater flow history in the northern part of the Baltic Artesian Basin (BAB) from the end of the Late Pleistocene to current conditions based on the hydrogeological studies carried out in 2012-2020 by the Department of Geology, Tallinn University of Technology and its partners. Hydrogeochemical data and various numerical models are combined in order to understand the link between glaciations and groundwater flow. The results of our earlier research and published literature on groundwater flow history in the BAB are also taken into account. The reconstruction of groundwater flow history is based on the database of the isotopic, chemical and dissolved gas composition of groundwater. The database contains data on 1155 groundwater samples collected during 1974-2017. We find that groundwater in the BAB is controlled by the mixing of three distinct water masses: interglacial/modem meteoric water (delta O-18 approximate to 11 parts per thousand), glacial meltwater (delta O-18 <= -18 parts per thousand) and an older syngenetic end-member (delta O-18 >=-4.5 parts per thousand). The numerical modelling has suggested that the preservation of meltwater in the northern part of the BAB is controlled by confining layers and the proximity to the outcrop areas of aquifers. Aquifers containing groundwater of glacial origin are in a transient state with respect to modern topographically-driven groundwater flow conditions. The most important topics for future research that can address gaps in our current knowledge are also reviewed.